The desired sensation level multistage input/output algorithm. - Scollie S; Seewald R; Cornelisse L; Moodie S; Bagatto M; Laurnagaray D; Beaulac S; Pumford J (Trends in Amplification, 2005)
The Desired Sensation Level (DSL) Method was revised to support hearing instrument fitting for infants, young children, and adults who use modern hearing instrument technologies, including multichannel compression, expansion, and multimemory capability. The aims of this revision are to maintain aspects of the previous versions of the DSL Method that have been supported by research, while extending the method to account for adult-child differences in preference and listening requirements. The goals of this version (5.0) include avoiding loudness discomfort, selecting a frequency response that meets audibility requirements, choosing compression characteristics that appropriately match technology to the user's needs, and accommodating the overall prescription to meet individual needs for use in various listening environments. This review summarizes the status of research on the use of the DSL Method with pediatric and adult populations and presents a series of revisions that have been made during the generation of DSL v5.0. This article concludes with case examples that illustrate key differences between the DSL v4.1 and DSL v5.0 prescriptions.